ChemInform Abstract: Synthesis, Crystal Structure and Characterization of Trivacant‐Keggin‐Polyoxometalate‐Based Carbonyl Manganese Derivative. Issue 28 (July 2015) - Liu, Yinbao; Zhang, Yanhui; Ma, Pengtao; Dong, Yongkang; Niu, Jingyang; Wang, Jingping
Abstract (NH4)3H3 [{Mn(CO)3}(Mn(H2O)2)(Mn (H2O)3) (TeW9O33)]2·31H2O (I) is prepared by reaction of Na8(TeW9O33) with MnCl2 (70 °C, 20 min) followed by addition of Mn(CO)5Br in MeCN (70 °C, 1 h; 16% yield).